Shandon-Don McMillan and family with tour personnel, 6 a.m. breakfast, Feb. 27
Left to right: CarlBeck, McMillan's Son-in-law, McMillan, Mrs. Mcmillan, Mr. McPhee, McMillan's daughter, Myrna and John E. Jones